Perancangan dan Implementasi Aplikasi E-Katalog Kos-Kosan Berbasis Web di Dusun Batu Alang Menggunakan Metode Rapid Application Development (RAD) - anggraeni, lina; Nora Dery Sofya; Farida Idifitriani (STIKes Ibnu Sina Ajibarang, 2026)
The development of information technology has driven the need for a digital system to provide information on temporary housing, particularly boarding houses. In Batu Alang Hamlet, the process of searching and managing boarding houses is still dominated by conventional methods, resulting in information on prices, facilities, and room availability not being conveyed optimally. This study aims to design and implement a web-based boarding house e-catalog application as a concise information and data management medium for boarding houses. This application was developed using the Rapid Application Development (RAD) method using the PHP programming language and the Laravel framework. The main features provided include searching and filtering boarding houses, displaying boarding house details, online boarding house bookings, managing boarding house data by owners, uploading proof of payment, notifications, and seller reviews. System testing was conducted through Black-Box Testing and usability evaluation using a questionnaire. The results of the study indicate that the boarding house e-catalog application can facilitate boarding house searches for prospective tenants and increase the effectiveness of boarding house promotion and management by owners. Thus, this application is declared suitable for use as a boarding house information medium in Batu Alang Hamlet.